'ShambaShield'—Delivering inclusive finance and climate-smart solutions to Kenyan farmer - Vyas, Shalika (CGIAR System Organization, 2025)
Millions of resource-poor smallholder farmers feed and nourish the people of Kenya. Yet they face an ever-more unpredictable and extreme climate. ShambaShield is developing solutions that will integrate financial protection, edutianment and information services to equip half a million Kenyan farmers with the tools they need to thrive in a changing climate.